The Most Common Reasons for Health Care Provider Visits in Reproductive Aged Men Differ by Race and Age Stratification. Issue 3 (3rd May 2020) - Balasubramanian, Adithya; Zhang, Chiyuan A.; Spradling, Kyle; Eisenberg, Michael L.
Abstract: Introduction: We assessed common reasons for health care provider visits among reproductive aged men. Methods: We used the Optum® Clinformatics® Data Mart, a de-identified insurance claims database encompassing commercial and Medicare Advantage health plan data from all 50 states, to analyze men 20 to 49 years old who were enrolled between January 1 and December 31, 2017. Men with at least 1 health care provider visit were included and were stratified into age groups of 20 to 29, 30 to 39 and 40 to 49 years old. For each age group the top 100 urological and nonurological ICD-10 diagnosis codes were aggregated and assessed per unit of observation. Groups were further stratified by race. Descriptive statistics are presented in counts and percentages. Results: A total of 3, 027, 585 men 20 to 49 years old were enrolled in Optum Data Mart in 2017. Of these men 1, 915, 027 (63%) had at least 1 visit with a health care provider. Musculoskeletal pain was the top reason for visits across all age groups. Sexually transmitted diseases were the top urological complaint in men 20 to 29 and 30 to 39 years old. Sterilization was among the top reasons for visits in white men and was less common in black, Hispanic and Asian men. Testicular hypofunction was the most common urological complaint in men 40 to 49 years old and erectile dysfunction was also noted. Conclusions: We identified urological concerns as common drivers for reproductive aged men to visit providers. Urological issues including sexually transmitted diseases, testicular hypofunction and erectile dysfunction motivate these men to seek medical attention, with rates differing based on age and race.